Evidence for coiled-coil dimer formation by an Epstein-Barr virus transactivator that lacks a heptad repeat of leucine residues. - Flemington, E (1990)
Two regions of the Epstein-Barr virus (EBV) BZLF1 gene product, ZEBRA, share sequence homology with c-Fos, one of which corresponds to the DNA binding domain of c-Fos. ZEBRA does not, however, contain the heptad repeat of leucines present in the dimerization domains of leucine zipper proteins. Here it is shown that ZEBRA binds its recognition sites as a homodimer and that the region adjacent to the basic DNA binding domain is essential for dimerization. This region contains a 4-3 repeat of predominantly hydrophobic residues, which is precisely in register with the hydrophobic heptad repeat present in the leucine zipper proteins with respect to the basic DNA binding domain. A mutational analysis of ZEBRA supports a model for dimerization involving a coiled-coil interaction. These results indicate that a heptad repeat of leucines is not a structural requirement for formation of coiled-coil dimers by transcription factors.